Extreme desert dust storms and COPD morbidity on the island of Crete - Lorentzou, Christina (Int J Chron Obstruct Pulmon Dis, 2019)
INTRODUCTION AND OBJECTIVES: Short-term extreme increases in desert-derived particulate-matter with aerodynamic diameter below 10 μm (PM(10)) may affect emergency department (ED) visits due to COPD exacerbations. RESEARCH QUESTION: Our aim was to identify the effect of extreme increases in desert-derived PM(10) on ED visits for dyspnea and COPD exacerbations and on the related hospital admissions. METHODS: We performed a retrospective analysis of dyspnea-related ED visits and hospital admissions in Heraklion, Crete, during four consecutive storms of desert-derived PM(10) that happened during March 2018. We collected data from over 17,000 ED visits and recorded patients with atopic symptoms, COPD exacerbations, and dyspnea, as well as admissions to the departments of pulmonary medicine, internal medicine, and cardiology. PM(10) data were collected from a monitoring station in the same geographic area. RESULTS: Four desert dust storms were recorded during the study period with 238, 203, 1138, and 310 μg/m(3) average-daily PM(10) and 652, 308, 4262, and 778 μg/m(3) hourly mean day-peak PM(10,) respectively. There was no clinically important increase in total ED visits, total admissions or admissions to the departments of cardiology, pulmonary medicine, or internal medicine, during PM(10) peaks. However, during the desert dust storm with daily-average PM(10) above 500 μg/m(3), there was a striking increase in dyspnea-related ED visits (including COPD exacerbations, 3.6-fold increase), while there was no clinically important increase in non-asthma allergy-related ED visits. CONCLUSION: Extreme desert dust storm episodes may cause meaningful increases in ED visits for dyspnea and COPD exacerbations/admissions.